The relationship between ground wind direction and seasonal variation of rain attenuation at Ku band satellite broadcasting services - Siat, Ling Jong (2014)
This study is aimed to investigate the relationship between ground wind direction and the seasonal variation of rain attenuation based on one year of weather station data recorded in Universiti Teknologi Malaysia (UTM), Johor, Malaysia. Preliminary analysis of wind direction based on monsoon seasonal and their impact on rain field advection are carried out to clarify the characteristics of rain attenuation in monsoon season. It is found that rain attenuation is not only affected by the monsoon seasonal variation but it also depends on rain field advection which can be preliminary identified from the wind direction. Such information is useful for the system operators to apply appropriate site diversity techniques during heavy rain events to reduce the system outage in this particular equatorial region.